Evaluasi Pengaruh Geometri Jalan Angkut Terhadap Produktivitas Dump Truck pada Pengangkutan Batubara dari Loading Point ke Stockpile di Site Ampelu PT. Nan Riang Kecamatan Muara Tembesi Kabupaten Batanghari Provinsi Jambi - Nanda Oktafian; Sumarya Sumarya (Departemen Teknik Pertambangan FT UNP, 2018)
Abstract. PT. Nan Riang is a coal mining company located in Kecamatan Muara Tembesi, Kabupaten Batanghari, Provinsi Jambi. The daily coal production target is 2,000 tons / day, while the actual production is 1,216,148 tons / day. One of the factors that affect the non-achievement of production targets is the condition of the haul road. Based on observations in the field, the general condition of the haul road was bumpy and there were many materials scattered about and when they passed there were transport equipment which had to stop due to the narrow road. Based on geometric measurements of the actual haul road, the actual road width was between 8.4-18.79 meters while the theoretical width of the straight road was 12 meters. The actual bend road width ranges from 10.44-19.21 meters while theoretically the bend road width is 17 meters. The actual grade of road starts from 1.20% to 15.32% while the ideal road grade is 8%. The actual cross slope ranges from 0-131 mm / m. The cross slope value for a 12 meter road width is 0.04 and a height difference of 24 cm. The superelevation value for the 17 meter bend width is 0.05 and the height difference is 85 cm. After being evaluated, there were 2 straight road width segments that needed to be added in width, namely BC and CD segments and 3 bend road width segments, namely AB, FG, and HI segments, as well as decreasing grades in BC segment and EF Productivity of dump truck CWM 330 PS with conditions Actual amounted to 1,216,148 tons / day. Productivity of dump trucks CWM 330 PS after improvements in work efficiency are 1,884.02 tons / day. Theoretical productivity of dump truck CWM 330 PS after improvement in work efficiency and ideal road geometry is 2,246.12 tons / day.Keywords: Cycle Time, Road Geometry, Coal, Production, Work Efficiency.